Development of a combined engagement rate indicator for evaluating social media advertising efficiency - Roik, O. O.; Ovsyak, V. K. (Forestry Education and Science: Current Challenges and Development Prospects, 2024)
In the modern digital economy, social media advertising has become an integral tool for businesses seeking to connect with customers. However, evaluating its effectiveness remains a significant challenge. This thesis proposes the development of a Combined Engagement Rate Indicator (CERI) aimed at providing a comprehensive metric for assessing social media advertising efficiency. By integrating traditional engagement metrics—Engagement Rate (ER) and Engagement Rate by Reach (ERR)—with financial performance indicators, CERI offers a more holistic evaluation tool that reflects both user engagement and business outcomes.